2013
DOI: 10.4103/1110-7782.124982
|View full text |Cite
|
Sign up to set email alerts
|

Serum visfatin in chronic renal failure patients on maintenance hemodialysis: a correlation study

Abstract: Background and aim of work Endothelial dysfunction, atherosclerosis, and cardiovascular disease are strongly linked to chronic kidney disease. It has been hypothesized that visfatin may play an important role in uremia-related atherosclerosis and the relation between visfatin and endothelial dysfunction has been proved. We aimed to study and characterize the relation of visfatin to some clinical and biochemical parameters among chronic renal failure (CRF) patients on regular hemodialysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…HD patients had significantly higher level; with more than 10 folds of normal controls. This in agree with the study was done on 68 patients on HD patients compared with 22 healthy controls, showed a highly significant increase in serum visfatin in the CKD group on HD in comparison with the healthy control participants [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…HD patients had significantly higher level; with more than 10 folds of normal controls. This in agree with the study was done on 68 patients on HD patients compared with 22 healthy controls, showed a highly significant increase in serum visfatin in the CKD group on HD in comparison with the healthy control participants [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among laboratory data obtained, significant correlations were found mainly between serum triglycerides and visfatin serum level (r = 0.49, p = 0.0006). The similar positive correlation was found by others [ 7 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we demonstrated a statistically significant difference in serum TG, LDLc, and HDLc levels in the HD group compared to the control group. Previous studies ( 21 , 15 ) had similar results, showing that higher visfatin levels were associated with decreased GFR, increased serum triglyceride and LDL cholesterol levels, and impaired endothelial function. Therefore, one would expect an increased probability of cardiovascular events in CKD patients with elevated serum visfatin concentrations due to their increased levels of TG and their reduced level of HDL cholesterol ( 21 ).…”
Section: Discussionsupporting
confidence: 60%
“…This was in agreement with Mu et al who supported, at least in part, the role of visfatin in uremia-related atherosclerosis ( 21 ). However, Lotfy et al showed no significant correlation between serum visfatin and HDLc ( 15 ). IMT showed a statistically significant difference between HD and control group (p < 0.01), suggesting that visfatin may reflect the degree of atherosclerosis in the carotid vascular bed of HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation